2019
DOI: 10.1186/s12887-019-1519-2
|View full text |Cite
|
Sign up to set email alerts
|

Schoolbag weight carriage in Portuguese children and adolescents: a cross-sectional study comparing possible influencing factors

Abstract: Background Schoolbags and the consequences of carrying them, particularly those associated with overload, are often studied as a health concern. Modifications in gait and posture were reported when children carried loads that corresponded to more than 10% of their body weight (BW). The aims of this study were to verify the load that is carried by Portuguese students and how it is influenced by factors such as school grade, school schedule, lunch site, physical education, sex and body mass index (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…However, this limit is often exceeded [30,32]. For example, a recent study found that approximately two-thirds of the Portuguese children analysed, 10 and 15 years of age, carried loads greater than 15% of their body weight at least once a week [29]. Similar results were found by Brzek and colleagues [35] in children from 7 to 9 years old in Poland.…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…However, this limit is often exceeded [30,32]. For example, a recent study found that approximately two-thirds of the Portuguese children analysed, 10 and 15 years of age, carried loads greater than 15% of their body weight at least once a week [29]. Similar results were found by Brzek and colleagues [35] in children from 7 to 9 years old in Poland.…”
Section: Introductionmentioning
confidence: 68%
“…Mechanical forces influence vertebral growth [26], and high loading rates may have negative effects on bone health [27,28]. In this sense, growing children who use backpacks daily may be at risk, especially if they carry an excessive load, which is the norm [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations